1990
DOI: 10.1364/ol.15.000912
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility and energetics in optical computing

Abstract: Computer operations that conserve energy do not, from an information viewpoint, increase entropy and therefore have no minimum energy cost associated with them. An information-conserving operation must be reversible in principle; reversible optical gates inevitably incur losses. The energy per calculation may have many meanings, as we show. The energy expended by a single photon in a conservative optical operation is negligible, much less than kT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…We must somehow skip (in terms of measurable "garbage" bits) most of the steps. Only quantum computing [3][4][5][6][7][8][9] can do this.…”
Section: An Absolutely-creative Subconsciousmentioning
confidence: 99%
See 2 more Smart Citations
“…We must somehow skip (in terms of measurable "garbage" bits) most of the steps. Only quantum computing [3][4][5][6][7][8][9] can do this.…”
Section: An Absolutely-creative Subconsciousmentioning
confidence: 99%
“…In recent articles we have shown that some optical processors are uniquely and truly quantum mechanical [3][4][5][6][7][8][9]. They can be so constructed that they perform most of their computations virtually in the wave domain before we read the results photons in the particle domain.…”
Section: Wave Particle Duality Processorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent papers an interesting new concept has been proposed by Caulfield et al with regard to the computing capability of optical processors, [Caulfield and Shamir 1990;Caulfield, Shamir, Ludman and Greguss 1990]. The kTbarrier mentioned earlier is claimed not to be a real barrier, but can be much smaller than this, for the following reasons.…”
Section: Reversibility and Wave Particle Duality Processorsmentioning
confidence: 99%